Determinant Factors for Cattle Insurance as a Risk Management Strategy - Amelia Dwi Nugrahaini; Mashyuri Masyhuri; Any Suryantini (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2021)
Cattle farmers in Gunungkidul Regency face several cattle diseases such as Helminthiasis, Anthrax, Downer Cow Syndrome, and Intoxication in which these diseases mostly attack female cows. To prevent financial loss for the farmers, the government facilitates them with cattle insurance. This study aims to determine the reasons and the cattle farmers’ willingness-to-pay for the cattle insurance by conducting a survey addressed to 100 cattle farmers and identifying the factors related to it. This study used a Contingent Valuation Method in estimating the cattle farmer's WTP. The various factors that influence the farmer's WTP were analyzed by using natural logarithm regression models. Based on the results of the study, it was found that the willingness-to-pay for cattle farmers who did not participate in cattle insurance are 22,600 IDR and farmers who participate in cattle insurance are 36,320 IDR. Education, household income, and farmers’ interest in the insurance were positively effecting toward the farmers' willingness-to-pay. However, age and the number of families showed the negative ones toward the farmers’ willingness-to-pay.